2016
DOI: 10.1523/jneurosci.2520-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent Conductances Drive Infraslow Intrinsic Rhythmogenesis in a Subset of Accessory Olfactory Bulb Projection Neurons

Abstract: The accessory olfactory system controls social and sexual behavior. However, key aspects of sensory signaling along the accessory olfactory pathway remain largely unknown. Here, we investigate patterns of spontaneous neuronal activity in mouse accessory olfactory bulb mitral cells, the direct neural link between vomeronasal sensory input and limbic output. Both in vitro and in vivo, we identify a subpopulation of mitral cells that exhibit slow stereotypical rhythmic discharge. In intrinsically rhythmogenic neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 96 publications
9
32
0
Order By: Relevance
“…Intriguingly, despite the expression of I h , none of the recorded MCs, in either group exhibited subthreshold resonance. Furthermore, while I h has also been observed in AOB MCs (data not shown; but see Gorin et al, 2016), we did not observe subthreshold resonance in recorded AOB MCs ( n = 5) nor in AOB PGCs ( n = 4).…”
Section: Resultssupporting
confidence: 41%
See 1 more Smart Citation
“…Intriguingly, despite the expression of I h , none of the recorded MCs, in either group exhibited subthreshold resonance. Furthermore, while I h has also been observed in AOB MCs (data not shown; but see Gorin et al, 2016), we did not observe subthreshold resonance in recorded AOB MCs ( n = 5) nor in AOB PGCs ( n = 4).…”
Section: Resultssupporting
confidence: 41%
“…However, it has been suggested that MOB MCs exhibit gamma-frequency subthreshold resonance due to a persistent Na + current (Brea et al, 2009), which was not addressed in our studies. Even in the AOB, I h has been described in MCs, but blocking it had no effect on the intrinsic oscillations of MCs (Gorin et al, 2016). In agreement with these findings, we found no I h -mediated subthreshold resonance in AOB MCs.…”
Section: Discussionmentioning
confidence: 99%
“…We observed less evoked spiking activity in MCs in AOB slices taken from post-behavior resident males than no-intruder controls (repeated measures ANOVA, interaction between group and stimulus, F(59,1298)=2.45, p<0.0001, n=13 cells, 4 mice for "intruder" group; n=9 cells, 4 mice for "no intruder" group, Fig. 7B-C Importantly, these currents are much smaller than those observed in IGCs, consistent with recent observations in mitral cells (Gorin et al, 2016). These results confirm that male-male social chemosensory encounters are associated with subsequent MC suppression, consistent with an experience-dependent increase in IGC-MC inhibition.…”
Section: Responses To Glomerular Stimulation Are Suppressed Followsupporting
confidence: 89%
“…6C, D). We first found that resting membrane potentials in EGCs (-86.0 mV ± 1.5 mV, n=13) were significantly hyperpolarized compared to MCs (-61.3± 1.0 mV, n=11), confirming earlier results (Gorin et al, 2016;Maksimova et al, 2019). In current clamp mode, standardized ramps of current injection resulted comparable maximal spike frequencies in EGCs (22-32 Hz, n = 4) and MCs (16-34 Hz, n = 5; Fig.…”
Section: Egc and Mcs Gcamp6f Signals Differentially Report Electrophysupporting
confidence: 85%